An Investigation into the Failure of Born Global Firms Internationalisation: A case of a USA based Firm - FASEYITAN, ABIOLA C. (2017)
ABSTRACT Researches have been conducted on the internationalisation strategy and the application of various models of born global firms in recent years. A vast number of this study has focused mainly on their internationalisation success integrating their major theories which are networking theory and resource based view theory. However, this studies takes another dimension. This thesis explored the reasons for the failure of born global firms. An in-depth study was carried out. The entrepreneurial model of internationalisation was focused upon to understand born global firm failures. It explores a case study approach using a USA based firm to understanding the reasons for their failure. The major highlights for the failure of born global firms are highlighted from the inadequacies entrepreneurial knowledge, entrepreneurial networking, entrepreneurial resources and external entrepreneurial factors. These factors were critically analysed with the application of supporting theories and finding from the case study. Solutions to these factors were proposed, and other relating factors were also analysed. This analysis was guided by a proposed theoretical framework to aid the analysis. The area where further studies were applicable were highlighted.